Pedagogical Strategies Used by English Teacher Educators to Overcome the Challenges Posed by Emergency Remote Teaching During the COVID-19 Pandemic - Castañeda-Trujillo, Jairo Enrique; Jaime Osorio, María Fernanda (Íkala, Revista de Lenguaje y Cultura, 2021)
The crisis in the education system generated by the appearance of covid-19 revealed the multiple gaps that exist due to the diversity of contexts to which students and teachers belong. This article reports on a case study which explored the challenges English teacher educators (tes) at a public university in Neiva, Colombia faced during the pandemic due to the imposition of emergency remote teaching (ert), the pedagogical strategies they used to respond to these challenges, and the ones that remain. To do this, data were collected from a questionnaire and a focus group with tes and pre-service teachers (psts) from the language teacher education program. The main findings show that the transition from classroom teaching to ert brought some challenges for tes and their trainees related to the social realities existing in the context of the latter. To respond to these challenges, tes had to adjust their teaching strategies and learn to use some technologies such as videoconferencing software and educational apps. Still some challenges remain for the future, such as enhancing pst’s motivation, autonomy and classroom interaction. The study suggests the need to continue training language tes on the use of ert technologies and to find more and better ways to promote autonomous learning processes to adapt teaching practices to current times.